LEXICAL DENSITY AND GRAMMATICAL INTRICACY IN SURAH AL-MULK - Novria Grahmayanuri; Linda Efrina Nasution; Ernila Sari Harahap; Ummu Ardhiyah (Universitas Muhammadiyah Muara Bungo, 2024)
This study focuses on analyzing lexical density and grammatical intricacy in surah Al-Mulk theorized by Ur and Halliday to identify the level of lexical density and grammatical intricacy involed by means of descriptive qualitative method. The data source of the research are Surah Al-Mulk taken from Quran Kemenag (KEMENTERIAN AGAMA RI, 2557). Surah Al-Mulk is the 67th surah of Holy Qur’an that has 30 verses. All verses of the letter al-Mulk are said to belong to the group of Makkiyah verses (surah which was released in Mecca). The data in this research are lexical item for analyzing lexical density and clauses for analyzing grammatical intricacy. The results of the research show that Lexical Density found surpasses 63%. It indicates that Surah Al-Mulk accounts for higher lexical density. It demonstrates the amount of information of existence of Allah and His Perfect Knowledge and Power by inviting people to reflect on the marvels of this universe. The number of Grammatical Intricacy of Surah Al-Mulk is 4.03. It is due to the high number of clauses towards the sentences. The analysis shows that the more grammatical Intricacy of Surah Al-Mulk, the language that is used is more complex.